The scale-up of microbial batch and fed-batch fermentation processes - Christopher Hewitt; Alvin W. Nienow (2010)
Micro-organisms are important for both human health and to industry so the fed-batch cultivation of microbial strains, often over expressing recombinant or natural proteins, to high cell density has become an increasingly important technique throughout the field of biotechnology, from basic research programmes to large-scale pharmaceutical production processes (Hewitt et al., 1999). The scale-up of such a process is usually the final step in any research and development programme leading to the large-scale industrial manufacture of such products by fermentation (Einsele, 1978). It is important to understand that the process of scaling-up a fermentation system is frequently governed by a number of important engineering considerations and not simply a matter of increasing culture and vessel volume. Therefore, it is perhaps surprising when the large-scale does not perform as well as the small-scale laboratory process. It is often observed that the biomass yield and any growth associated products are often decreased on the scale-up of an aerobic process (Enfors et al., 2001). For Saccharomyces cerevisiae, the biomass yield on molasses increased by 7% when the process was scaled-down from 120 m3 to 10 l even when a seemingly identical strain, medium and process were employed (George et al., 1993). In an E. coli fed-batch recombinant protein process, the maximum cell density reached was found to be 20% lower when scaling-up from 3l to 9 m3 and the pattern of acetic acid formation had changed. (Bylund et al., 1998). During another study (Enfors et al., 2001), the performance of a recombinant strain of E. coli during fed-batch culture was found to vary on scale-up from the lab-scale to 10-30 m3 industrial bioreactors. This included lower biomass yields, recombinant protein accumulation and surprisingly perhaps a higher cell viability. These findings are typical of those found when scaling up most fermentation processes yet only a few mechanisms have been presented that can satisfactorily explain these phenomena. In this Chapter, we will briefly discuss the main engineering considerations involved in fermentation scale-up and then critically review those mechanisms thought to be responsible for any detrimental change in bioprocessing at the largerscale. Though it addresses mainly E. coli fed-batch fermentations, much of the discussion also applies to batch and other single celled aerobic microbial fermentations too.